Rekonstruksi Kebijakan Hukum Kenaikan Uang Kuliah Tunggal Berdasarkan Tanggung Jawab Konstitusional Negara - Endrianto Bayu Setiawan (Lex Renaissance, 2024)
The policy of state universities to increase the Single Tuition Fee (Uang Kuliah Tunggal, hereinafter UKT) has an impact on the community's ability to access higher education. This is because the higher the UKT, the more difficult it will be for the community to access education at the State Universities. This study establishes two problem formulations. First, how is the guarantee of the fulfillment of citizens' constitutional rights through the regulation of UKT financing? Second, how is the reconstruction of the legal policy for increasing UKT so that it provides a sense of justice for the community based on the concept of the state's constitutional responsibility? This study is normative with a conceptual approach and laws and regulations. The results of the study conclude two points. First, the high UKT imposed on the community is a form of neglect of the state's constitutional responsibility to fulfill citizens' constitutional rights to education. The 1945 Constitution of the Republic of Indonesia expressly regulated the allocation of a large budget for the fulfillment of accessible education, especially for the State Universities. Second, the government needs to reconstruct the legal policy so that UKT is in line with the mandate of the constitution by evaluating regulations and arranging the distribution and refocusing of the higher education budget. The short-term policy that needs to be carried out is to change Permendikbudristek No. 2 of 2024 which is the legal basis for the increase in UKT. Then, long-term policies need to evaluate the status of PTN-BH (the State Universities-Legal Entity) as stated in Law No. 12 of 2012 and Government Regulation No. 26 of 2015 in conjunction with Government Regulation No. 8 of 2020.Keywords: Right to Education, State Responsibility, Single Tuition Fee AbstrakKebijakan perguruan tinggi negeri yang menaikkan tarif uang kuliah tunggal (UKT) berdampak terhadap kemampuan masyarakat untuk mengakses pendidikan tinggi. Sebab, semakin tinggi UKT akan menyulitkan masyarakat dalam mengakses pendidikan di PTN. Penelitian ini menetapkan dua rumusan masalah. Pertama, bagaimana jaminan pemenuhan hak konstitusional warga negara melalui pengaturan pembiayaan UKT? Kedua, bagaimana rekonstruksi kebijakan hukum kenaikan UKT supaya memberikan rasa keadilan bagi masyarakat berdasarkan konsep tanggung jawab konstitusional negara? Penelitian ini bertipe normatif dengan pendekatan konseptual dan peraturan perundang-undangan. Hasil penelitian menyimpulkan dua poin. Pertama, tingginya UKT yang dibebankan kepada masyarakat merupakan bentuk pengabaian tanggung jawab konstitusional negara untuk memenuhi hak konstitusional warga negara atas pendidikan. UUD NRI 1945 telah mengatur secara tegas adanya alokasi anggaran yang besar untuk pemenuhan pendidikan yang aksesibel, terutama untuk PTN. Kedua, pemerintah perlu melakukan rekonstruksi kebijakan hukum supaya UKT sejalan dengan amanat konstitusi dengan melakukan evaluasi regulasi serta menata distribusi dan refocusing anggaran pendidikan tinggi. Kebijakan jangka pendek yang perlu dilakukan adalah mengubah Permendikbudristek No. 2 Tahun 2024 yang menjadi dasar hukum kenaikan UKT. Kemudian, kebijakan jangka panjang perlu mengevaluasi status PTN-BH yang tertuang dalam UU No. 12 Tahun 2012 dan PP No. 26 Tahun 2015 jo. PP No. 8 Tahun 2020.Kata Kunci: Hak Atas Pendidikan, Tanggung Jawab Negara, Uang Kuliah Tunggal